A study of the factors influencing the utilization of family planning methods in urban slums of Allahabad district, Uttar Pradesh, India - Setu, Yachna; Prakash, Shiv; Parveen, Khurshid; Singh, Richa (International Journal Of Community Medicine And Public Health, 2018)
Background: India was the first country to launch National Family Planning Program in 1952, but still the country’s desired total fertility rate and contraceptive prevalence rate have not achieved. The use of family planning methods is better in urban areas as compared to rural areas and it is worse in urban slums. Objective of the stud was to find out the utilization pattern of family planning methods and identifying the factors influencing it. Methods: A community based cross sectional study was carried out on eligible couples selected from urban slums of Allahabad district by multistage random sampling and were interviewed by using pre-tested schedule. Data analysis was done by using SPSS version 21. Results: A total of 356 eligible couples (age 15-49 years) were surveyed for a period of one year. It was observed that 45.78% (163/356) of eligible couples were using any of the family planning method and most commonly used method was female sterilization (53.98%), followed by condom (18.40%), then IUCDs (13.49%), injectables, OCPs and Natural methods (approx 4%) use. The use of family planning methods was found to be associated with women’s age, duration of marriage, caste categories, men’s education status, number of living children. Conclusions: The use of family planning methods is low in slums areas and to improve the condition awareness should be created.